2016
DOI: 10.1186/s12890-016-0182-8
|View full text |Cite|
|
Sign up to set email alerts
|

Graphic analysis of flow-volume curves: a pilot study

Abstract: BackgroundConventional spirometric parameters have shown poor correlation with symptoms and health status of chronic obstructive pulmonary disease (COPD). While it is well-known that the pattern of the expiratory flow-volume curve (EFVC) represents ventilatory dysfunction, little attempts have been made to derive quantitative parameters by analyzing the curve. In this study, we aimed to derive useful parameters from EFVC via graphic analysis and tried to validate them in patients with COPD.MethodsUsing Graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…However, spirometry alone is inadequate in distinguishing which patients may benefit from LAMA therapy. Previous studies have shown that graphical analysis of SEFV curve can be useful in identifying progressive expiratory flow limitation (Lee et al, 2016;Ma et al, 2010) and correlates better with clinical parameters, such as the 6-minute walk test distance, than do traditional spirometric values (Lee et al, 2016). This study is the first to investigate whether the SEFV curve changes with interventions that are designed to improve expiratory flow.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, spirometry alone is inadequate in distinguishing which patients may benefit from LAMA therapy. Previous studies have shown that graphical analysis of SEFV curve can be useful in identifying progressive expiratory flow limitation (Lee et al, 2016;Ma et al, 2010) and correlates better with clinical parameters, such as the 6-minute walk test distance, than do traditional spirometric values (Lee et al, 2016). This study is the first to investigate whether the SEFV curve changes with interventions that are designed to improve expiratory flow.…”
Section: Discussionmentioning
confidence: 89%
“…During exercise in COPD, as hyperinflation develops, the elastic recoil decreases lengthening the expiratory time constants of these lung units, necessitates increased intrathoracic pressure to maintain flow. Greater expiratory pressures augment gas compression and dynamic airway compression, leading to a progressive fall in expiratory flow, which manifests as concavity in the spontaneous expiratory flow-volume (SEFV) curve (Lee et al, 2016;Ma et al, 2010;Varga et al, 2016). Expiratory flow limitation contributes to dynamic hyperinflation during exercise, whereby the end-expiratory lung volume progressively increases and inspiratory capacity (IC) and inspiratory reserve volume are reduced, and which is associated with dyspnea and exercise intolerance in COPD (O'Donnell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…
The original version of this article [1] was unfortunately missing funding information within the acknowledgements section.The work was Supported by grant no 11-2008-038 from the SNUBH Research Fund. Med.
…”
mentioning
confidence: 99%
“…The original version of this article [1] was unfortunately missing funding information within the acknowledgements section.…”
mentioning
confidence: 99%
“…O equipamento comparava valores de fluxo pulmonar, correlacionando os valores li-dos com parâmetros aceitos na sociedade médica, dando um resultado instantâneo do paciente, que pode ser interpretado pelo médico que acompanha.Conforme (MORETO TRINDADE; LINS FAGUNDES DE SOUSA; LUIS PEREIRA ALBUQUERQUE, 2015), "A espirometria é a principal ferramenta funcional respiratória e deve persistir por várias décadas." Este mesmo autor menciona que a morfologia das curvas devem constar do diagnóstico funcional, e o nosso trabalho apresenta resultados numéricos para auxiliar neste estudo morfológico e que podem ser num futuro utilizado para uma maior precisão do diagnóstico.Conforme escrito em(LEE et al, 2016), parâmetros da espirometria convencionais têm demonstrado fraca correlação com os sintomas e estado de saúde de doença pulmonar obstrutiva crônica (DPOC). Embora seja bem conhecido que o padrão da curva de fluxo-volume expiratório (CVF) representa uma disfunção ventilatória, pequenas tentativas têm sido feitas para derivar os parâmetros quantitativos por meio da análise da curva.…”
unclassified